2018
DOI: 10.1039/c8md00315g
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of boron-containing compounds as Aβ aggregation inhibitors and antioxidants for the treatment of Alzheimer's disease

Abstract: A novel series of boron-containing compounds were designed, synthesized and evaluated as multi-target-directed ligands against Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 30 publications
6
32
0
Order By: Relevance
“…Although we did not measure the boron levels in the TBSA-treated mice brain tissue, previous studies have shown that boron compounds can cross the blood brain barrier and penetrate the brain tissue [ 32 ] and decrease inflammatory responses [ 33 ]. Combined with previous research showing efficacy of boron compounds in the brain [ 3 , 4 , 5 , 6 , 7 ], our findings of the efficacy of TBSA in the present study strongly suggest that TBSA is sufficiently permeable to brain tissue to reduce AD pathology.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Although we did not measure the boron levels in the TBSA-treated mice brain tissue, previous studies have shown that boron compounds can cross the blood brain barrier and penetrate the brain tissue [ 32 ] and decrease inflammatory responses [ 33 ]. Combined with previous research showing efficacy of boron compounds in the brain [ 3 , 4 , 5 , 6 , 7 ], our findings of the efficacy of TBSA in the present study strongly suggest that TBSA is sufficiently permeable to brain tissue to reduce AD pathology.…”
Section: Discussionsupporting
confidence: 88%
“…Although as a trace element, boron has yet to be established as an essential nutrient for humans, recent experimental and clinical studies suggest that it might be an important mineral for cell membrane function [ 7 ]. Because of their anti-inflammatory properties, boron compounds have been used as dietary supplements for the treatment of neuroinflammation and in neurodegeneration [ 4 ]. Boron compounds have been tested to treat a host of disorders, from arthritis to vascular dysfunction [ 13 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This important characteristic enabled the development of specic enzyme inhibitors that can be used for Alzheimer's disease and cancer treatments. [11][12][13] For instance, the peptidylboronic antineoplastic agent Bortezomib has been used in cancer treatment since 2003. 14 Phenylboronic acid (PBA) belongs to a class of organic ligands that are widely employed for molecular recognition.…”
Section: Introductionmentioning
confidence: 99%